األلعاب اللغوية في تعليم اللغة العربية في املدارس االبتدائية في برنامج جي قاف(J-QAF)في ماليزيا : دراسة تحليلية = Al-al'aab al-lughawiyah fii ta'liim al-lughah al-arabiyah fii al-madaaris al-ibtidaiyah fii barnaamaj (j-qaf) fi Malaysia : dirasah tahliliyah - Chik, Abdul Rahman (IMLA, 2015)
This research aims to find out how the use of language games and their impact in the educational attainment of the primary school students in the Arabic language education in the j-QAF program, and also aims to identify the extent of the application of the proposed model language games existing models in the textbooks. Find and reach the conclusion that this program a new educational program applied by some teachers using language games, and this program has a strong impact on the educational achievement of primary school students in the teaching of Arabic, Malaysia.